Design, Manufacture, and Test of a Taperless 6-Bladed Horizontal Axis Wind Turbine (HAWT) with 1 Meter Diameter - Aslam Ghiffary, Azzufar
Indonesia is the country with the largest primary energy consumption in Southeast Asia and the fifth largest in the Asia Pacific. However, the increase in primary energy consumption is causing anxiety in Indonesian society. This can disrupt the sustainability and security of national energy. This condition encourages Indonesian people to use renewable energy. Renewable energies that have been used are solar energy, wind energy, and water energy. Wind can be used as an alternative to substitute the fossil fuels. The average wind speed in Indonesia is relatively low, which is around 5.5 m/s. More and more micro scale wind turbines that can spin faster at low wind speeds causing more wind energy to be utilized in Indonesia. Therefore, the design, manufacture, and testing of horizontal axis wind turbines with six blades with a diameter of 1 meter has been done. The rotor in this wind turbine is designed to be able to rotate at low wind speeds and can produce optimum coefficient of performance at low to medium wind speeds. During the testing, not only the wind turbine rotor was tested, but also the generator. From the test results, the maximum power obtained is 62.05 W, far different from the design results, namely 236.72 W. This wind turbine has a power coefficient (ratio of electrical power produced to wind power received) of about 0.05. The start-up speed of this wind turbine is 2.9 m / s, the cut-in speed is 9 m / s, and the cut-out speed is 13.5 m / s.